A Sopron – Fertőd térség turisztikai helyzetértékelése - Söveges Dávid (2019)
The tourism as an economic branch, has one of the highest rate of dinamic growth world wide. It’s importance and variety of tools are constatly growing and changing. Today’s developed societies’ most relevant economic problem is the determination and observation of the economival sustainable growth. The tourism has great opportunities within the branch, by increasing the consumption of services we can maximise the pace of development, yet minimise the negative external effects of the industry. However we supposed to obtain projects frt the volumenal increase of the consumption of the touristic products, the usageof the local environmental and natural resources. We have to obtain better knowledge about the basic consumption behaviors and motivations, their internal and external chain mechanism of affections and the upcoming opportunities. The touristical attraction basis and the projected image of the mentioned area is supposed to be hearded towards the most relevant consumers on the market. When we examine the interraction of the systematical components of tourism and their multiplication mechanism affection, we can achieve several conclusions which makes us capable to obtain higher rates of progression. My thesis below is supposed to assess the touristical situation circulated around the Sopron – Fertőd area and the causation of the potentionally upcoming problems. The examination of the touristical system elements of the town of Sopron and their general affect towards the local economy. The rate of progression will be compared with the national average, further more the relative and absolute progression levels with the realistic potential. The hypothesis meant to forecast the underperformance according to the expectations of the touristical progression of the area. will be examined by the order of the previously mentioned angle and this way I am going to try to prove my point about the problem. After I could isolate the causation, I am going to make a development proposal, and value the present ongoing development projects in the are in this matter.